MAKNA SIMBOLIK MOTIF NAGA BESAUNG PADA KAIN SONGKET DI FIKRI SONGKET KOTA PALEMBANG - Bagus, Unggul; Misnawati, Desy (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
In general, songket is a cloth woven using gold or silver thread and is produced from certain areas such as Palembang, Jambi. From Bali, Minangkabau to Samarinda, the word songket comes from the word sungkit which means to lift the thread, while in a special sense, sungkit is a needle made of bone used for embroidery. This research was conducted to examine the motifs of songket cloth in the city of Palembang. This type of songket is full of elements of symbols of majesty or greatness for the bride and groom and the general public who wears it. The dragon besaung motif is a symbol of a mythological animal that is believed by the Chinese people to have spiritual values ​​that symbolize strength, luck, goodness and prosperity. This study tries to explain the meaning contained in the dragon besaung motif, analyzed using qualitative methods. Data collection techniques are by observation, interviews, documentation. Using Pierce’s semiotics study approach technique, seen from the triangle meaning. The results of the study concluded that the dragon besaung motif is considered by the people of Palembang to symbolize love and peace.